Pelatihan Komprehensif Desain Mesin Berbasis Teori - Wedhasari, Tyas; Ruhyat, Nanang; Multahada, Erna (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
ABSTRACTThis community service activity aimed to enhance the capacity of micro, small, and medium enterprise partners in the manufacturing sector through theoretical-based machine design training. This training is distinctive because, in addition to mechanics and design theory, the material also covers production management and digital marketing concepts, providing participants with a comprehensive perspective on operational processes and business strategies. The implementation method involved a series of training modules covering fundamental machine design principles using mechanics and materials, Computer-Aided Design software utilization, production management, and digital marketing. The training was conducted in Malaysia with active participation from partner participants, students, and lecturers. The activity results demonstrated a significant improvement in participants' theoretical understanding and practical skills in machine design, modern technology application, as well as production management and marketing. Initial evaluation through surveys and feedback indicated that the capacity building targets were successfully achieved. In conclusion, this activity provided a tangible contribution to improving the human resources quality of the partners, potentially enhancing their business competitiveness in the market.ABSTRAKKegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas mitra, yaitu pelaku usaha kecil dan menengah di sektor manufaktur, melalui pelatihan pembuatan desain mesin dengan pendekatan teoretis. Pelatihan ini berbeda karena tidak hanya teori mekanika dan desain, materi juga mencakup konsep manajemen produksi dan pemasaran digital, memberikan peserta perspektif menyeluruh tentang proses operasional dan strategi bisnis. Metode pelaksanaan meliputi serangkaian tahapan pelatihan desain mesin menggunakan prinsip dasar mekanika dan material, pemanfaatan perangkat lunak Computer-Aided Design, manajemen produksi, serta pemasaran digital. Pelatihan dilaksanakan di Malaysia dengan melibatkan peserta mitra, mahasiswa, dan dosen. Hasil kegiatan menunjukkan peningkatan pemahaman teoretis dan keterampilan praktis peserta dalam desain mesin, penggunaan teknologi modern, serta manajemen produksi dan pemasaran. Evaluasi awal melalui survei dan umpan balik menunjukkan tercapainya target peningkatan kapasitas. Simpulan kegiatan ini memberikan kontribusi nyata terhadap peningkatan kualitas sumber daya manusia mitra, yang berpotensi meningkatkan daya saing usaha mereka di pasar.